A predicted sex pheromone receptor of codling moth Cydia pomonella detects the plant volatile pear ester - Bengtsson, Jonas M.; Gonzalez, Francisco; Cattaneo, Alberto M.; Montagné, Nicolas; Walker, William B.; Bengtsson, Marie; Anfora, Gianfranco; Ignell, Rickard; Jacquin-Joly, Emmanuelle; Witzgall, Peter (Frontiers in Ecology and Evolution, 2014)
Plant volatiles mediate host discrimination and host finding in phytophagous insects. Understanding how insects recognize these signals is a current challenge in chemical ecology research. Pear ester, ethyl (E,Z)-2,4-decadienoate, is a powerful, bisexual attractant of codling moth Cydia pomonella (Lepidoptera, Tortricidae) and strongly synergizes the male response to female-produced sex pheromone. We show here that the codling moth odorant receptor (OR) CpomOR3 is dedicated to detecting this plant volatile. Heterologous expression of CpomOR3 in Drosophila T1 trichoid and ab3A basiconic sensilla, followed by a screening with codling moth pheromone compounds and known plant volatile attractants, confirms that CpomOR3 binds to pear ester. Although CpomOR3 does not respond to any of the pheromone components tested, a phylogenetic analysis of lepidopteran chemosensory receptor genes reveals a close relationship of CpomOR3 with pheromone receptors (PRs) in moths. This corroborates the interaction of ecological and social chemosensory cues during premating communication. The finding that a plant volatile compound, pear ester, is a specific ligand for a PR-like lepidopteran receptor adds to our understanding of insect-plant interactions and emphasizes the interaction of natural and sexual selection during the phylogenetic divergence of insect herbivores.